Angels of light, powers of darkness thinking Biblically about angels, Satan and principalities - Noll, Stephen F. (Downer's Grove, IL IVP, 1998)
Includes bibliographical references and indexes.
Keywords: Demonology -- Biblical teaching; Devil -- Biblical teaching; Angels -- Biblical teaching